Elk-boat Depictions in the Ethnoarchaeological Context - Mykhailova, Nataliia (Archaeologia Lituana, 2022)
Numerous depictions of elk-shaped ships are discovered in rock art of the Northern Europe and Siberia, dating from the Mesolithic time to the Bronze age. Usually they are interpreted as Boats of the Deads, connecting the Worlds. The water is the symbol of a border between Worlds in traditional societies. Northern Europe archaeological findings prove that images of the Cervid as a mediator between Worlds and the Boat of the Deads became connected in the Stone Age. Red deer (Cervus Elaphus) remnants were found in burials from the Mesolithic period to the Iron Age. Cemeteries of humans in boats with deer antlers or elk-headed stuffs were discovered at the Mesolithic sites of Denmark (Vedbaeck, Mollegabet) and in Northern Russia (Bolshoy Oleniy Ostrov). Being of a great significance in the mytho-ritual complex of the Stone Age population in Europe, Elk-Boat as the transport between Worlds is preserved in folklore of South-East European people. Mythological motif of the Cervid, sailing on the Sea or the River, with the sleeping maiden on his antlers, is widespread in South and Eastern Europe.
Keywords: Mesolithic; Neolithic; Northern Eurasia; rock art; cervidae; cult of the deer; elk-headed boats; boat of the dead